Reducing Surgeon's Physical Stress in Minimally Invasive Neurosurgery - Nakayashiki, Atsushi; Kawaguchi, Tomohiro; Nakagawa, Atsuhiro; Mochizuki, Fusako; Furukawa, Hiroaki; Nagai, Arata; Suematsu, Takuya; Tominaga, Teiji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background and Study Aims Various minimally invasive approaches are used in neurosurgery. Surgeons must perform nondynamic fine movements in a narrow corridor, so specially designed surgical devices are essential. Unsophisticated instruments may pose potential hazards. The purpose of this study was to assess the factors associated with muscle fatigue during minimally invasive neurosurgery and to investigate whether physical stress can be reduced by refining the devices used.Material and Methods Four physical aspects of a handpiece were investigated: torque of conduits (0.20, 0.28, and 0.37 kgf*cm), shape of hand grip (five types), angle of the nozzle (0, 20, and 40 degrees), and weight balance (neutral, proximal, and distal). To evaluate muscle fatigue, surface electromyography was recorded from the extensor carpi radialis muscle and flexor carpi radialis muscle during a geometric tracing task. The maximum voluntary contraction (MVC) of each muscle and %MVC (muscle contraction during a task/MVC × 100) were used as the indexes of muscle fatigue.Results The shape of the hand grip significantly reduced %MVC, which is associated with muscle fatigue. The torque of conduits and angle of the nozzle tended to reduce muscle fatigue but not significantly. Weight balance did not affect muscle fatigue. Based on these results, we made two refined models: model α (torque of conduits 0.2 kgf*cm, angle of nozzle 20 degrees, neutral balance, hand grip with a 2.9 × 2.0-cm oval section with angled finger rest), and model β (torque of conduits 0.2 kgf*cm, angle of nozzle 20 degrees, neutral balance, hand grip with a 2.9-cm round section with a curved finger rest). The %MVC was significantly decreased with both types (p < 0.05 and p < 0.01, respectively), indicating reduction of muscle fatigue.Conclusions The geometrically refined surgical device can improve muscle load during surgery and reduce the surgeon's physical stress, thus minimizing the risk of complications.
Keywords: muscle fatigue; stress reduction; pulsed water jet; medical device development